Efektivitas Pelayanan Publik Di Dinas Perumahan Permukiman Dan Pertanahan Kabupaten Bulukumba (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to find out the implementation of public services in the Department of Housing, Settlements and Land, Bulukumba Regency. This study used qualitative research, the source of data used primary and secondary, the number of informants was 11 people. Data collection techniques used observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, qualitative competitive data verification, and data triangulation source validation, source triangulation sources, tehniques, and time. The results of this study showed that public effectivenessbib the Department of Housing, Settlement and Land of Bulukumba Regency were classified as effective and some were not yet effective, which were discussed in terms of (1) service procedures, in accordance with existing service procedures, but not yet effective; (2) completion time, provision of business services was completed on time, but not yet effective; (3) service costs, were already classified as effective; (4) facilities and infrastructure, already classified as effective; (5) employee competencies, had been classified as effective.